2023
DOI: 10.1111/hex.13705
|View full text |Cite
|
Sign up to set email alerts
|

The use of arts‐based methodologies and methods with young people with complex psychosocial needs: A systematic narrative review

Abstract: Background Arts‐based methodologies and methods (ABM) can elicit rich and meaningful data with seldom‐heard groups and empower participants in research. Young people with complex psychosocial needs could be better engaged in research using arts‐based approaches to overcome communication and literacy issues as well as distrust of those with power, including researchers. A critical review of the use and impact of ABM among this population is timely. The purpose of this review is to synthesize and examine the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…First, the pathways approach offers opportunities to adopt and incorporate new forms of engaged scholarship, such as the use of arts-based research, enabling the co-construction and co-production of knowledge. Emerging research in this area points to the power of arts, narration, and story-telling in the capturing, meaning-making, and thoughtful interpretation of individuals with lived experience of homelessness [96][97][98]. For example, in one study, Moxley and Feen [96] demonstrated how storytelling by women experiencing homelessness revealed different pathways, with arts-based methods allowing for a deeper understanding through the photovoice technique.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…First, the pathways approach offers opportunities to adopt and incorporate new forms of engaged scholarship, such as the use of arts-based research, enabling the co-construction and co-production of knowledge. Emerging research in this area points to the power of arts, narration, and story-telling in the capturing, meaning-making, and thoughtful interpretation of individuals with lived experience of homelessness [96][97][98]. For example, in one study, Moxley and Feen [96] demonstrated how storytelling by women experiencing homelessness revealed different pathways, with arts-based methods allowing for a deeper understanding through the photovoice technique.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…It is possible that this reflects barriers to planning and implementing projects involving younger children. These barriers may include, for example, restrictions on time, effort and funding, institutional and ethical requirements to suitably accommodate younger children, 9,13,95,96,99,[106][107][108]112,113 as well as perceptions that younger children are less competent or capable of contributing value to research. 46,96,98,102,103 Another confounding factor is how involvement of younger children is reported within the literature.…”
Section: Risk Of Bias/quality Assessmentmentioning
confidence: 99%
“…Globally, it is estimated that one in seven 15-to-24-yearolds (14%) experiences a mental health disorder; anxiety and depressive disorders are the most common with a global prevalence of 3.4% and 4.6% respectively (Institute for Health Metrics and Evaluation, 2019;World Health Organization, 2021). Arts-based methods have been used in youth mental health research (Abdulla, Abdulla, & Liamputtong, 2021;Atayero et al, 2020;Boydell, 2011;Boydell et al, 2016;Nathan et al, 2022). Topics explored include anxiety Woodgate, Zurba & Tennent, 2017a, 2017b, depression (Sawyer & Earle, 2019;Willis et al, 2018), and suicide (Keller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…ABM can facilitate accessing thoughts and experiences on sensitive topics and provide more nuanced perspectives than other research methods as they allow for creative exploration and expression of experiences in ways other than the usual verbal means (Austin & Forinash, 2005; Casey & Webb, 2019; Gerber et al, 2022). Arts-based methods are thus useful when working with children, youth, and young adults as these methods can address literacy issues, distrust of those in power, and facilitate communicating about topics young people may find difficult to discuss (Nathan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%